2006
DOI: 10.1007/s10265-006-0038-z
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic and biochemical activities in flag leaves of a newly developed superhigh-yield hybrid rice (Oryza sativa) and its parents during the reproductive stage

Abstract: Responses of net photosynthetic rates to intercellular CO(2) concentration (P (n)/C (i) curves) and photochemical characteristics were investigated in flag leaves of newly developed superhigh-yield hybrid rice (Oryza sativa L.) LiangYouPeiJiu (LYPJ) and its maternal PeiAi64S (PA64S) and paternal WuMang9311 (WM9311) lines grown in the field during the reproductive stage. The results showed that photosynthetic functions, such as the electron transport activities of photosystems and photophosphorylation, assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 33 publications
3
22
0
1
Order By: Relevance
“…Photophosphorylation activity is the capacity of chloroplasts to produce ATP under light conditions, using light energy to transform ADP into ATP (Zhang et al, 2007), a reaction catalyzed by ATP-synthase in chloroplast thylakoid membranes. The altered photophosphorylation activity suggests that Cr 6+ treatment of rice seedlings decreases the capacity of chloroplasts to produce ATP and transform light energy into chemical energy (Fig.…”
Section: Photosynthesis Is Inhibited Under Cr 6+ Stressmentioning
confidence: 99%
“…Photophosphorylation activity is the capacity of chloroplasts to produce ATP under light conditions, using light energy to transform ADP into ATP (Zhang et al, 2007), a reaction catalyzed by ATP-synthase in chloroplast thylakoid membranes. The altered photophosphorylation activity suggests that Cr 6+ treatment of rice seedlings decreases the capacity of chloroplasts to produce ATP and transform light energy into chemical energy (Fig.…”
Section: Photosynthesis Is Inhibited Under Cr 6+ Stressmentioning
confidence: 99%
“…The CO 2 assimilation rate measured in rice, wheat (Triticum aestivum), and Arabidopsis hybrids shows no increase in photosynthesis rate per unit leaf area in the hybrids compared with the inbred parents (Yang et al, 2007;Zhang et al, 2007;Fujimoto et al, 2012), but hybrid plants with their greater leaf area and increased number of chloroplasts have a greater total photosynthetic capacity (Fujimoto et al, 2012).…”
Section: Phenotypes Of Hybrid Plantsmentioning
confidence: 99%
“…Recent studies have suggested that the differentially expressed genes and proteins between the wheat hybrids and their parents involved in diverse physiological process pathways, including metabolism, materials transport, photosynthesis, and signal transduction, could play important roles for hybrids (Yao et al, 2005;Wang et al, 2006;Song et al, 2009). In rice, it has been demonstrated that higher photosynthetic activities in the hybrid than in its parents in the mid and late stages may be responsible for its super-high-yield (Zhang et al, 2007(Zhang et al, , 2010. A serial analysis of gene expression study in rice indicated that the higher yield in a hybrid may be due to up-regulated genes involved in carbon-and nitrogen-assimilation, including photosynthesis in leaves (Bao et al, 2005).…”
Section: Discussionmentioning
confidence: 98%